Management of Jakarta Metropolitan Medical Center Hospital in Preventing Burnout in Nurses during the Covid-19 Pandemic - Chintia, Amelia; Ede Surya Darmawan (Biomedical Journal of Indonesia, 2021)
Introduction. The COVID-19 pandemic has caused considerable losses to the health care system in Indonesia. The Indonesian Doctors Association (IDI) noted that as of October 3, 2020, 130 doctors, nine dentists, and 92 nurses died due to COVID-19. The problems that caused the death of health workers during the COVID-19 pandemics included the lack of PPE, inadequate patient screening in health facilities, and fatigue of medical personnel due to the increasing number of COVID-19 patients as long working hours and psychological pressure. Of course, this condition can disrupt the quality of life and work productivity in the health series. Therefore, the hospital needs to make various efforts to prevent burnout in health workers during the COVID-19 pandemic. Methods. This research was a descriptive method with quantitative and qualitative approaches. The researcher revealed the facts that occurred when the study was running and presented them as they were. The research respondents were nurses who were in the isolation room and ICU COVID-19 at MMC Hospital Jakarta. Researchers used the Maslach Bach Inventory (MBI) questionnaire instrument to 43 respondents via the Google form. Researchers also conducted interviews with the Head of Nursing and several COVID-19 nurses who had filled out questionnaires. Results: The majority of COVID-19 nurses at MMC Hospital had moderate burnout levels. MMC Hospital Jakarta has made various efforts to prevent burnout in nurses. Conclusion: Management of MMC Hospital in preventing burnout in nurses was good enough, but several points can be improved to make it better.